Analysis of residual water reuse practices: case study in industrial laundry - Souza, Mariane Cásseres; Vargas, Andrea; Saueressig, Gislaine Gabriele; Luchese, Juliane; Bauer, Jéssica Mariella; Viegas, Cláudia Viviane (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Water is an abundantly used input in industrial laundry processes. The reuse of water in effluent treatment plant reduces costs and brings environmental benefits, that is, an eco-efficiency factor. This study aims to analyze the practices of water reuse in industrial laundries on its effluent treatment plants. In this regard it was studied two medium-sized companies in the field of industrial laundries located in southern Brazil. The research method used was multiple case study. The results show the decrease in the polluting load with the water recycling process with consequent cost reduction. The application of technologies and substances used without harming the environment with the use of wet washing and dry cleaning has been observed. From the results, a vision of best practices is proposed found in water reuse benefits associated with the management of cleaner production in terms of eco-efficiency.